2015
DOI: 10.3109/14992027.2015.1020972
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frequency compression on music perception

Abstract: Although less frequency compression was in general preferred, there was more variability in the comparisons involving the default settings for a 50-dB hearing loss (i.e. start frequency 4000 Hz, compression ratio 2.5:1) and no compression, suggesting that mild amounts of compression may not be detrimental to perceived sound quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Why this particular question showed significant differences, in the absence of effects of processing condition on the speech perception tasks, is unclear. The lack of an overall effect on the remainder of survey items is consistent with the equivocal sound quality results with nonlinear frequency compression using conservative settings (Bohnert et al, 2010;Parsa et al, 2013;Brennan et al, 2014;Mussoi and Bentler, 2015).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Why this particular question showed significant differences, in the absence of effects of processing condition on the speech perception tasks, is unclear. The lack of an overall effect on the remainder of survey items is consistent with the equivocal sound quality results with nonlinear frequency compression using conservative settings (Bohnert et al, 2010;Parsa et al, 2013;Brennan et al, 2014;Mussoi and Bentler, 2015).…”
Section: Discussionsupporting
confidence: 64%
“…Others have reported that listeners with hearing loss do not rate the quality of speech differently from conventional processing across a range of frequency compression settings, with the exception of poorer ratings for conditions with a start frequency of compression below 2 kHz (Parsa et al, 2013). Music perception has been reported to be either unaffected (Parsa et al, 2013;Brennan et al, 2014) or negatively affected (Mussoi and Bentler, 2015) by nonlinear frequency compression, with poorer ratings associated with more aggressive frequency compression settings (Mussoi and Bentler, 2015). The overall pattern of results suggests that conservative frequency-lowering settings may not negatively affect perceived sound quality but that lower start frequencies and more aggressive compression ratios do have the potential to negatively impact sound quality.…”
mentioning
confidence: 98%
“…However, the cutoff frequency in such hearing aids is usually chosen to be above 2000 Hz, and people are relatively insensitive to mistuning between the lower harmonics and the very high harmonics [85]. Results from a recent study suggest that mild amounts of frequency compression with a high cutoff frequency do not adversely affect music perception, but stronger compression or lower cutoff frequencies have detrimental effects [86].…”
Section: Special Music Programs and Other Hearing Aid Featuresmentioning
confidence: 99%
“…It is important to note, however, that the listeners in the study of Mussoi and Bentler did not present with severe or profound hearing loss. 18 Therefore, the results may not generalize to the population of interest in this article. Fig.…”
mentioning
confidence: 95%
“…16,17 Findings for music perception suggest ratings are unaffected, on average, 14,17 or are negatively affected by stronger settings. 18 This relates to the concept of FL, which is aimed at improving audibility of high-frequency sound, but introduces distortion to the aided signal. It is important to note, however, that the listeners in the study of Mussoi and Bentler did not present with severe or profound hearing loss.…”
mentioning
confidence: 99%